Penerapan Metode Kompresi Wavelet dalam Pengolahan Data Gambar untuk Mengurangi Ukuran File - Ni Putu Suci Paramita,; I Gede Arta Wibawa, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
Currently more and more computer users the increase in the number of computer users has led to an increase digital data user. One of the most used digital data today is digital images. The smallest element of a digital image is called pixels. The higher the number of pixels, the higher the digital resolution picture. The higher the pixel count, the larger the digital image file size. Resulting in fast full data storage capacity.Image data compression is an important process in data processing and storage, especially with the increasing use of images in various applications and platforms. This study aims to apply the Wevalet compression method in processing image data to reduce file size. The Wevalet compression method combines the wavelet transform with an adaptive and efficient compression breaking procedure, to form significant compression without significant sacrifice of image quality.
Keywords: images, compression, Wevalet